The Transcendent Unity Behind the Diversity of Religions and Religiosity in the Perspective of Perennial Philosophy and Its Relevance to the Indonesian Context - Baharudin, M.; Luthfan, Muhammad Aqil (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This study is conducted to answer an important question: is there any transcendent unity behind the diversity or plurality of religions and religiosity? This question will be answered through perennial philosophy approach. The study found that, according to perennial philosophers, there is a transcendent unity behind the diversity or plurality of religions and religiosity. This transcendent unity is seen in âthe common visionâ, or what in Islam is called the âbasic message of religionâ, namely âsubmissionâ to always fear God and live His presence in everyday life. Further, the perennial philosophers argue that the True God is one; therefore, all religions emerging from the One are in principle the same for they come from the same source. In other words, the diversity of religions and religiosity lies only in the exoteric level, and all religions actually have a transcendent unity in the esoteric level. However, in this case, the perennial philosophers do not mean to unify or equate all religions. In fact, they try to open a way to a spiritual ascent through the reviving of the religious traditions in every religion.Penelitian ini dilakukan untuk menjawab sebuah pertanyaan penting: adakah kesatuan transenden di balik keragaman atau pluralitas agama dengan religiusitas? Pertanyaan ini akan dijawab melalui pendekatan filsafat perennial. Penelitian ini menemukan bahwa, menurut para filsuf perennial, ada kesatuan transenden di balik keragaman atau pluralitas agama dan religiusitas. Kesatuan transenden ini terlihat dalam pandangan bersama, atau apa yang di dalam Islam disebut pesan dasar agama, yaitu tunduk untuk selalu takut kepada Tuhan dan menjalani kehadiran-Nya dalam kehidupan sehari-hari. Selanjutnya, para filsuf perennial berpendapat bahwa Tuhan yang Sejati adalah satu. Oleh karena itu, semua agama yang muncul dari Yang Satu pada prinsipnya sama karena mereka berasal dari sumber yang sama. Dengan kata lain, keragaman agama dan religiusitas hanya terletak pada tingkat eksoteris, dan semua agama benar-benar memiliki kesatuan transenden di tingkat esoteris. Namun, dalam kasus ini, filsuf perennial tidak bermaksud menyatukan atau menyamakan semua agama. Sebenarnya, mereka mencoba membuka jalan menuju pendakian spiritual melalui kebangkitan kembali tradisi keagamaan di setiap agama.